Tribological characterization of recycled basalt-aramid fiber reinforced hybrid friction composites using grey-based Taguchi approach. (1st March 2019) - Manoharan, S; Vijay, R; Singaravelu, D Lenin; Krishnaraj, S; Suresha, B
Abstract: Fibers play an imperative role in determining the tribological behavior of reinforced friction composites. The objective of the present study is to develop recycled basalt and recycled aramid fiber reinforced hybrid friction composites with the addition of various fillers and optimize the tribological behaviors of the composites. The pin-on-disc test rig was used to conduct dry sliding wear following Taguchi's L27 orthogonal array with process parameters of the applied load, sliding speed and the weight percentage of fiber content. Grey relational analysis was adopted for tribological parameters optimization, satisfying multiple performance characteristics. Analysis of variance was used to find the contribution of individual factors that affect tribological behavior. Optimal parameter combination for multi-response characteristics of the friction composite under investigation was applied a load of 15 N, sliding speed of 1 m s −1 and composite with 25 weight percent of fiber content. The results showed that addition of fiber content significantly increased wear resistance of the friction composites. Further, from the scanning electron microscopy images of friction and wear tested friction composites, plateau formation, fiber-matrix debonding, fiber pull out, cracks and damage on the matrix and various wear mechanism were identified.